ChemInform Abstract: Addition of Thiols to o‐Quinone Methide: New 2‐Hydroxy‐3‐phenylsulfanylmethyl [1, 4]Naphthoquinones and Their Activity Against the Human Malaria Parasite Plasmodium falciparum (3D7). Issue 21 (2nd May 2013) - Sharma, Abhinay; Santos, Isabela O.; Gaur, Pratibha; Ferreira, Vitor F.; Garcia, Celia R. S.; da Rocha, David R.
Abstract None of the investigated compounds (III) exhibit better performance than respected control drugs.